Hedonisme Clubbers dalam Nightclub Studi Kasus Pandemi Covid-19 di Kelurahan Seminyak - Gultom, Agus SyahPutra; Suwena, I Wayan; Suarsana, I Nyoman (Sunari Penjor : Journal of Anthropology, 2022)
When clubbers want to enter a nightclub they must know the rules that apply in a club. The applicable rules are in the form of the type of clothing worn, minimum age, luggage that is allowed to be brought into the club. In the nightclub will be seen the characteristics, form of activity, and factors of attending a nightclub. The Covid-19 pandemic that is destroying much of the economy especially against club owners taking some action to save the existence of his club. With this formulation of the problems in this study are: 1. What are the characteristics, lifestyle forms of clubbers hedonism as well as factors that affect clubbers visiting a nightclub? 2. What is the situation of the night club in the midst of the Covid-19 Pandemic?. The method used in this study is qualitative as a support. The data sources used are types of primary and secondary data sources obtained through observations, interviews, literature studies, and documents. The analysis used is descriptive analysis. The study used David Chaney's theory of lifestyle and Jean P. Baudrillard's theory of consumerism .